Trastorno de ansiedad y su repercusión social en una joven de 20 años de edad del cantón Montalvo - Gomez Gonzalez, Gissela Stefania (2022)
In this case study, the impact of anxiety on the social development of a 20-year-old girl from Montalvo canton will be determined. Since social interactions arise as a human need, because human beings by nature have depended on this characteristic for survival. To carry out this case, techniques such as clinical interview, psychometric evaluation test Beck Anxiety Inventory BAI and Hamilton Anxiety Scale were applied, which helped to determine the diagnosis of the present patient, where established according to DSM-5 Social anxiety disorder (social phobia) with code f40.10 and According to ICD-10 Social phobia disorder with code f40.1, to treat this case the use of psychotherapy was implemented based on in Cognitive Behavioral Therapy CBT. With which he had a great connection between practice and theory, since this pathology was not presented as something positive or negative, but rather as the interpretation of the stimuli that caused the patient to manifest the situations in his life as overwhelming. work, the same ones that stimulated the appearance of certain symptoms, which generated a shock in their personal and professional growth. It is mentioned that, based on the proposed psychotherapeutic scheme, the final results were satisfactory and favorable for the patient.